ANALISIS PEMETAAN KESUKAAN KONSUMEN PADA PRODUK KERIPIK TEMPE ORIGINAL DI KALANGAN MAHASISWA FAKULTAS PERTANIAN UNIVERSITAS RIAU - Febrianto, Wegi Eko; Restuhadi, Fajar; Rossi, Evy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research is to know the position of the product and the best original tempe chips attributes from various kinds of original tempe chips are used, such as Qtela Tempe Chips, Ayu Bersaudara Tempe Chips, N & R Tempe Chips, Puspa Malay Tempe Chips, Reza Snack Tempe Chips, Big One Chips, MAK Snack Tempe Chips, Winda Snack Tempe Chips. It aims to determine the level of consumer preference to a product. In addition there is still a lack of effort in developing products towards the manufacturer at this time. This research is conducted by mapping methods of internal and external preferences with objects of eight different product types. Sensory analysis used was hedonic and descriptive test. The results of cluster analysis of hedonic test and the main component analysis of the descriptive test were then analyzed by using the preference mapping technique, with the sensory attributes used in tempe chips products were greasy, oily, savory, bitter, salty, crispy, brittle, thick, soybean, rancid, From the results of the analysis conducted, the Qtela tempe chips products, Ayu Bersaudara tempe chips and Winda Snack tempe chips most favored by the panelists.keyword: Original Tempe Chips, AHC, PCA, Preference Mapping